English Learning Strategy as Foreign Language Relating to Demographic Factors on First Grade Cadets of POLTEKBANG - Laila Rochmawati; Aris Wijanarko; Fatmawati Fatmawati; Meita Maharani S. (Jurnal Penelitian)
The determing of language learning strategies that are often used by cadets in the Surabaya aviation polytechnic and knowing the correlation between the age, gender, major and educational background of each cadet are the goals in this reseach. Chi-Square test and Pearson product moment correlations test was used in order to determine whether or not common effect of age, gender, major and educational background of each cadet displayed significant differences on Language Learning Stratrgy of students. The results stated that the most frequently-used strategies were metacognitive strategies. The least frequently-used ones were affective strategies. The results of Pearson product moment correlations revealed that gender were the only demografic factors that were significantly correlated with the learners’ learning strategy. The relationship between learners’ learning strategy and gender was found to be positively significant .002 (sig < .005), learning strategy use associated with gender were significantly correlated.